Prevention Model of Disguised Crime in Indonesian Banking Facing the Deviation Actions of The Credit Use/Side Streaming by Debtor; Theoretical Review On Risk Management Of Default Due To Side Streaming - Yani, Mas Ahmad; Mustofa, Muhammad (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2019)
AbstractThe purpose of this paper is to explore and conduct systematical research through reading materials (researching by reading) on the possibility of prevention steps to prevent or reduce the Deviation Actions of the Credit Use (Side Streaming) by Debtor in the Problem of Banking Credit Facilities Utilization in Indonesia. This paper is constructed by referring to one step of researching conducted by Ian Crow and Natasha Semmens in “Researching Criminology” (2006). It is stated that in researching by reading there are three approaches, they are (1) process of literature review; (2) process of reading and utilizing other people research findings; and (3) process of data analysis which is not used in researches, for example data taken from a writing in a newspaper or other mass media called content analysis. This research concludes that although the mode has been regulated in Law of Crime, the actions of side streaming have not been set up in banking crime actions in Indonesia. For the time being, side streaming occurs due to the availability of chances or opportunities and the possibility of using it to hide fraudulent misrepresentation actions.Keyword: Prevention, Side streaming, Criminal Banking AbstrakTujuan dari makalah ini adalah untuk mengeksplorasi dan melakukan penelitian sistematis melalui bahan bacaan tentang kemungkinan langkah-langkah pencegahan atau mengurangi tindakan penyimpangan Penggunaan Kredit (Side Streaming) oleh Debitur dalam Masalah pemanfaatan fasilitas kredit Perbankan di Indonesia. Makalah ini dibangun dengan mengacu pada satu langkah penelitian yang dilakukan oleh Ian Crow dan Natasha Semmens dalam